Bis-indolyl benzenoids, hydroxypyrrolidine derivatives and other constituents from cultures of the marine sponge-associated fungus aspergillus candidus KUFA0062 - Buttachon S. (2018)
A previously unreported bis-indolyl benzenoid, candidusin D (2e) and a new hydroxypyrrolidine alkaloid, preussin C (5b) were isolated together with fourteen previously described compounds: palmitic acid, clionasterol, ergosterol 5,8-endoperoxides, chrysophanic acid (1a), emodin (1b), six bis-indolyl benzenoids including asterriquinol D dimethyl ether (2a), petromurin C (2b), kumbicin B (2c), kumbicin A (2d), 2”-oxoasterriquinol D methyl ether (3), kumbicin D (4), the hydroxypyrrolidine alkaloid preussin (5a), (3S, 6S)-3,6-dibenzylpiperazine-2,5-dione (6) and 4-(acetylamino) benzoic acid (7), from the cultures of the marine sponge-associated fungus Aspergillus candidus KUFA 0062. Compounds 1a, 2a–e, 3, 4, 5a–b, and 6 were tested for their antibacterial activity against Gram-positive and Gram-negative reference and multidrug-resistant strains isolated from the environment. Only 5a exhibited an inhibitory effect against S. aureus ATCC 29213 and E. faecalis ATCC29212 as well as both methicillin-resistant S. aureus (MRSA) and vancomycin-resistant enterococci (VRE) strains. Both 1a and 5a also reduced significant biofilm formation in E. coli ATCC 25922. Moreover, 2b and 5a revealed a synergistic effect with oxacillin against MRSA S. aureus 66/1 while 5a exhibited a strong synergistic effect with the antibiotic colistin against E. coli 1410/1. Compound 1a, 2a–e, 3, 4, 5a–b, and 6 were also tested, together with the crude extract, for cytotoxic effect against eight cancer cell lines: HepG2, HT29, HCT116, A549, A 375, MCF-7, U-251, and T98G. Except for 1a, 2a, 2d, 4, and 6, all the compounds showed cytotoxicity against all the cancer cell lines tested. © 2018 by the authors